A utilização de BIM para o levantamento de quantitativos: estudo de caso de uma estação elevatória de esgoto de grande porte - Sousa, Rafael Winicius da Silva e (Universidade Federal do Tocantins, 2022)
The sanitation sector in Brazil needs investments so that the sewage collection and treatment rates are evenly distributed and increased among the regions of the country. Therefore, it is essential to invest efficiently and sustainably, and this can be corroborated by the use of Building Information Modeling (BIM) Sewage Pumping Station (EEE) projects. important units in sewage transportation. The overall objective of the paper is to evaluate the use of BIM technology in the survey of project quantitative data from a large EEE, in order to compare the budgeted quantities produced from a Computer Aided Design (CAD) with the quantities extracted from Autodesk® Revit® software after EEE modeling. The delimitation of the work was based on the items of preliminary services, general services, earthmoving, structure, waterproofing, hydraulic materials, equipment, architectural materials and equipment and the assembly of the pipes. The results show a difference of 7% less than the cost obtained through the use of BIM in relation to the budgeted cost through the CAD project. The major differences were in the earth movement, which presented a 25% less divergence, and in the concrete structure, which presented a 7% more discrepancy from the value automatically obtained with the BIM tool compared to the manually quantified value CAD assistance. The modeling of the EEE in a BIM environment allowed us to evaluate the compatibility of the disciplines involved in the project and to more assertively control the quantity of material. Thus, it is observed that the adoption of the BIM methodology in the Sewage Pumping Station projects was effective to obtain a more assertive quantitative survey.